PENGURANGAN KECEMASAN ANAK YANG MENJALANI INHALASI DENGAN PERMAINAN BONEKA KARAKTER - Romantika, I Wayan; Jasmin, Muh.; Hasrima, Hasrima; Rosjidi, Cholic Harun; Andas, Amzal Mortin (Universitas Sam Ratulangi, 2023)
Background :Anxiety is one of the first impacts of a child's hospitalization. This becomes very important to deal with when children cannot overcome their anxiety in a timely manner, they tend to resist treatment, and care, are afraid, embarrassed, and lose independence. Therefore, appropriate treatment is needed to reduce the anxiety response. There are many ways to reduce anxiety in children, one of which is play therapy. Objective :This study aims to determine the effect of stuffed toy therapy on anxiety in hospitalized children. Method :The design of this study was pre-experimental with a one-group pretest-posttest approach. The research sample was obtained by applying the Simple Random Sampling method and 17 respondents were selected. Results :The Spearman Rank test results obtained a p-value of 0.001. Conclusion :character play doll therapy significantly reduces anxiety in inpatient children aged 3-5 years. Keywords: anxiety; character dolls; play therapy